Factors influencing mortality in covid-19-associated mucormycosis - the international ID-IRI study - Şahin, Meyha; Yılmaz, Mesut; Mert, Ali; Naghili, Behrouz; Ravanbakhsh, Fatemeh; Varshochi, Mojtaba; Alavi Darazam, Ilad; Ebrahimi, Mohammad Javad; Moafi, Maral; Tehrani, Hamed Azhdari; Mahboob, Amjad; Rashid, Naveed; et al. (My University, 2024)
The emergence of COVID-19, caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), triggered a global pandemic. Concurrently, reports of mucormycosis cases surged, particularly during the second wave in India. This study aims to investigate mortality factors in COVID-19-associated mucormycosis (CAM) cases, exploring clinical, demographic, and therapeutic variables across mostly Asian and partly African countries. A retrospective, cross-sectional analysis of CAM patients from 22 medical centers across eight countries was conducted, focusing on the first three months post-COVID-19 diagnosis. Data collected through the IDI-IR included demographics, comorbidities, treatments, and outcomes. A total of 162 CAM patients were included. The mean age was 54.29±13.04 years, with 54% male. Diabetes mellitus (85%) was prevalent, and 91% had rhino-orbital-cerebral mucormycosis (ROCM). Surgical debridement was performed in 84% of the cases. Mortality was 39%, with advanced age [Hazard Ratio (HR)=1.06, (p<0.001)], rituximab use (HR=21.2, p=0.05), diabetic ketoacidosis (HR=3.58, p=0.009) identified as risk factors. The mortality risk increases by approximately 5.6% for each additional year of age. Surgical debridement based on organ involvement correlated with higher survival (HR=8.81, p<0.001). The utilization of rituximab and diabetic ketoacidosis along with advancing age, has been associated with an increased risk of mortality in CAM patients. A combination of antifungal treatment and surgical intervention has demonstrated a substantial improvement in survival outcomes.
Keywords: COVID-19; COVID-19-Associated Mucormycosis; Immunosuppression; Mortality